ANALISIS PRODUKTIVITAS DAN PENDAPATAN KELAPA SAWIT PETANI PLASMA DAN SWADAYA DI SUMATERA SELATAN - Lifianthi; Oktarina, Selly; Rosana, Elly (Agripita Publisher, 2018)
The oil palm plantation business system for Musi Banyuasin (Muba) and Ogan Komering Ilir (OKI) is divided into two: the people's own smallholders (swadaya) and smallholders' plantation system (plasma), based on the plantation business managed by smallholders and self-help farmers, the management of oil palm can be seen from the pattern of production factor utilization and the production of both plantation systems. Factor of production is very determine the size of production produced, that is in the form of Fruit Fruit Bunch (TBS). Factors used are land area, fertilizer, herbicide and labor. Based on the result of the research, there are differences in the pattern of cultivation between plasma and self-help in both districts. The election of these two districts is due to the fact that the oil palm plantation is quite large compared to other districts managed by smallholders and self-help farmers. The results of the research indicate that there is a difference in the pattern of production factor utilization, which draws on the pattern of farming use of production factors in Muba Regency, where self-employed farmers in Urea and KCL use more than plasma farmers. While in OKI Regency in its herbicide use very little once per year. Production and income earned respectively show the difference between plasma farmers and self-help with the same plant age between 20 to 21 years.